Serum amyloid A concentration may reflect HDL functionality. (June 2013) - Nofer, Jerzy-Roch
Evaluation of: Dullaart RP, de Boer JF, Annema W, Tietge UJ. The inverse relation of HDL anti-oxidative functionality with serum amyloid A is lost in metabolic syndrome subjects. Obesity 21, 361–366 (2013). Antiatherogenic functions exerted by HDLs are impaired in coronary heart disease and other pathologic conditions associated with increased cardiovascular risk; however, the direct assessment of HDL functionality is challenging. In the evaluated study, Dullaart et al. report the inverse association between plasma serum amyloid A (SAA) concentrations and the capacity of HDL to inhibit LDL oxidation in healthy individuals, but not in patients with metabolic syndrome. These findings provide the first indication that SAA determination might be helpful as an indirect measure for the antioxidative capacity of HDL. However, the utility of SAA measurement as a proxy for HDL functionality may be limited to certain populations.